Evil and the God of Love - Hick, J. author. aut Link
XX, 389 p.
Keywords: When first published, Evil and the God of Love instantly became recognized as a modern theological classic, widely viewed as the most important work on the problem of evil to appear in English for more than a generation. Including a foreword by Marilyn McCord Adams, this reissue also contains a new preface by the author.